Galileo probe interpretation indicating a neutrally stable layer in the Jovian troposphere. Issue 9 (14th May 2017) - O'Neill, Morgan E; Kaspi, Yohai; Fletcher, Leigh N.
Abstract: The sole in situ measurement of a giant planet atmosphere comes from the Galileo probe, which plunged through Jupiter's weather layer at 6.5°N and measured a remarkably stable atmospheric temperature profile. Horizontal winds were observed to substantially increase from 1 to 3 bars, in a region of relatively low static stability. We show that this high‐shear region indicates the best possibility of zero potential vorticity and resulting slantwise convection and suggest that the fluid here could potentially be adiabatic. We generalize an expression to determine lapse rates along constant angular momentum surfaces for deep atmospheres at any latitude. Key Points: The Galileo Probe observed a layer of air likely adjusted by slantwise convection from 1 to 3 bars The observed Galileo static stability in the 1‐3 bar layer is misleading and actually neutral A full scale height is therefore neutral to dry convection in the "hot spot" location of the Galileo Probe